STRATEGI FUNDRAISING BERBASIS KOMUNITAS; PELUANG DAN TANTANGAN (Studi Pada Unit Pengumpul Zakat (UPZ) Badan Amil Zakat (BAZNAS) Kota Kediri - Ma'mun, Mohamad Ma'mun (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2023)
Zakat is a maliyah worship that must be carried out by a rich Muslim who fulfils the conditions and is given to those who are entitled to receive zakat, especially for the poor and needy. Law No 23 of 2011 on zakat management authorises BAZNAS, Provincial, Regency or City BAZNAS to establish UPZ (Zakat Collection Unit) in government agencies, state-owned enterprises, private companies, regionally-owned enterprises, and can also establish UPZ at the sub-district, village or kelurahan level. One of the UPZ that has been formed and running is UPZ under BAZNAS Kota Kediri. The researcher used field research (fieldresearch) in this study. it is a qualitative approach. The analysis used is descriptive. Descriptive data presupposes that the data is in the form of text. Descriptive qualitative research is a study that describes the situation in the form of transip in interviews, written documentation. The result of this study are: BAZNAS Kediri City in conducting fundraising using several strategies, namely: a. Direct Fundraising, it is a method that uses a way or technique that directly involves the participation of muzakki. b. Indirect Fundraising, it is a method that does not directly involve the participation of muzakki, such as promotions that lead to the formation of an image or image of zakat institutions, without direct direction to donate Keyword: Strategy, Fundraising, Community